Design, production, burn-in and tests of the hybrid circuits of the Upstream Tracker at the LHCb detector. (1st May 2022) - Citterio, M.; Conti, N.; De Benedetti, F.; Gandini, P.; Merli, A.; Neri, N.; Petruzzo, M.; Spadaro Norella, E.
Abstract: We present a description of the design process, prototyping and production of the hybrid circuits for the front-end electronics of the Upstream Tracker at LHCb. The multilayer polyamide-based printed circuit boards, or hybrids, are designed to host the front-end ASICs. The ASICs require an optimized power delivery network from 0 to 120 MHz, with a maximum of 10 −2 Ohms round-trip resistance, and 100 Ohms differential traces. Hybrids are required to have minimal radiation length, and to withstand the harsh environmental conditions of the data taking through intrinsic radiation hardness characteristics.